BRAND EQUITY PT SAMSUNG ELECTRONIC INDONESIA DI KOTA BATAM - ANDY RAHMADY; ANGEL PURWANTI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The current competitive environment in the economy is quite tight and complex. Every company is required to always understand and comprehend what is happening in the market and what consumers desire, as well as the changes that exist to be able to compete with the competitors. This type of research is quantitative research that will examine the effect of brand equity consisting of, brand awareness, brand quality impression and brand associations on consumer loyalty. In sampling, researchers used the Simple Random Sampling technique. Respondents' responses to the brand equity variables are almost entirely good. This shows that, respondents believe in brand equity inherent in PT Samsung Electronic Indonesia.